The Effect of Aging Duration Meat of Madura Cattle on The Organoleptic Quality of Meatball Products - Umar, Malikah; Kurniati Agustina, Desi; Hidayati, Nurul; Mardiyah, Surrotul (Bantara Journal of Animal Science, 2024)
Meat handling and processing aim to extend the shelf life of meat and enhance its distinctive flavour, allowing consumers to enjoy processed meat in various forms and flavours. One of the most popular meat products is meatballs. Meatballs are made by mashing meat, adding spices and flour, shaping the mixture into small balls, and boiling them in hot water. The quality of the ingredients used determines the quality of meatballs, particularly the type and quality of the meat, the type of flour, and the ratio of ingredients in the dough. This study aims to determine the effect of the duration of Madura beef on the organoleptic properties of processed meatballs and to identify the duration that results in meatballs with the most favourable properties. The research variables included organoleptic tests, namely smcolourcolor, texture, and taste, with 30 respondents as replicates. The experimental design used was a Completely Randomized Design with four treatments: P1 (meatballs made from meat without ageing), P2 (meatballs made from meat aged for 6 hours), P3 (meatballs made from meat aged for 8 hours), and P4 (meatballs made from meat aged for 10 hours). The results were descriptively tested using hedonic methods. Data were analyzed using Analysis of Variance. The study showed no significant effect between treatments on smell, colour, texture, and taste in processed meatball products made from Madura beef aged for different durations.